Soft tissue sarcomas of the extremity and superficial trunk: do we need radiotherapy? - Chan, Lester Wai Mon (2024)
Soft tissue sarcomas (STS) are a heterogeneous group of mesenchymal malignancies with a propensity for local recurrence (LR) and metastasis. Surgical resection remains the cornerstone of management. Adjuvant radiotherapy (RT) reduces LR and current guidelines recommend RT for the majority of intermediate-to-high-grade tumours. The indications for RT, however, vary between centres.